Reaksi Pembentukan 17α(chlorovinyl-3-methyl-butene)estradiol Melalui Reaksi Adisi Alkuna Terminal Pada Etinilestradiol Dengan Katalis ZnCl2: Reaksi adisi alkuna terminal pada 17α-ethinylestradiol dengan Katalis ZnCl2 dan HCl dengan media diklorometana - Omega Siwu; Rymond J. Rumampuk; Budi Oktavia; Soenandar M.T Tengker; Vlagia I Paat; Emma J. Pongoh (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The addition reaction had been done on the terminal alkynes of 17α-ethynylestradiol with ZnCl2 and HCl catalyst mediated by dichloromethane. The reaction conditions were carried out at a temperature of 70°C for 29 h, the separation of the reaction properties was carried out using Gravity Column Chromatography, and the reaction products were identification using by Nuclear Magnetic Resonance (NMR). The catalyst used was a cationic ligand coordinate, where Zn acts as the central ion and 2-propanol as the ligand. In the reaction mechanism, the reaction begins with the formation of dimeric ether. ZnCl3 catalyst acts as Lewis acid which converts alcohol to dimeric ether and forms a complex with ZnCl3. The nucleophilic terminal alkyne then attacks the C-O bond of the ether to form a vinyl carbocation which then attracts a chlorine atom from ZnCl3 which was complex bound with ether, resulting in a reaction product of 17α(chlorovinyl-3-methyl-butene)estradiol